Bilateral facial nerve palsy as the sole initial symptom of syphilis: a case report. Issue 5 (13th July 2015) - Ting, Chi-Hsin; Wang, Chih-Wei; Lee, Jiunn-Tay; Peng, Giia-Sheun; Yang, Fu-Chi
Abstract: Bilateral facial nerve palsy is an exceedingly rare condition and presents a diagnostic challenge. Bilateral facial nerve palsy may result from cranial trauma, congenital abnormalities, inflammation, infiltration, or infection, but is rarely associated with syphilis. Here, we report a case of syphilis in which bilateral facial nerve palsy was the only initial symptom. A 22-year-old man presented at our emergency department with isolated bilateral facial nerve palsy. Results for initial serum and cerebrospinal fluid examinations were normal, including the rapid plasma reagin titer. One week later, the patient developed rashes on the torso, palms, and soles. At this time, a high serum rapid plasma reagin titer was detected, and the Treponema pallidum particle agglutination test was positive. Once the tests were confirmed, the patient admitted to a history of unprotected sexual behavior. Penicillin G treatment was effective, and a 3-month follow-up examination demonstrated a complete recovery. We recommend that syphilis be considered when diagnosing sexually experienced young men presenting with bilateral facial nerve palsy, even in the absence of skin manifestations. Failure to recognize facial signs of syphilis could result in inappropriate management, affecting the patient's clinical outcome. Résumé: La paralysie bilatérale du nerf facial est un trouble extrêmement rare, qui pose des difficultés de diagnostic. La paralysie bilatérale du nerf facial peut résulter d'un traumatisme crânien, d'anomalies congénitales, d'une inflammation, d'une infiltration ou d'une infection, mais elle est rarement associée à la syphilis. Sera exposé ici un cas de syphilis dans lequel la paralysie bilatérale du nerf facial était le seul symptôme initial de la maladie. Un homme de 22 ans est venu consulter au service des urgences pour une paralysie bilatérale et isolée du nerf facial. Les analyses sérologiques et l'examen du liquide céphalorachidien se sont révélés normaux au départ, y compris le test rapide de la réagine plasmatique. Toutefois, une semaine plus tard, des éruptions cutanées sont apparues sur le tronc, la paume des mains et la plante des pieds. Un titre élevé de réagine plasmatique a alors été détecté au test sérologique rapide, et l'épreuve d'agglutination passive de Treponema pallidum s'est avérée positive. Une fois les résultats confirmés, le patient a admis avoir eu un comportement sexuel risqué dans le passé. Le traitement par la pénicilline G a agi efficacement, et l'examen de suivi au bout de 3 mois a permis d'établir l'obtention de la guérison complète. Les auteurs recommandent donc que soit envisagé le diagnostic de syphilis chez les jeunes hommes ayant une vie sexuelle active et présentant une paralysie bilatérale du nerf facial, même en l'absence de manifestations cutanées. Le fait de ne pas reconnaître les signes faciaux de la syphilis pourrait conduire à une prise en charge inadaptée, et se répercuter sur les résultats cliniques.